Natural Polymers Used In In Situgelling Systems - Chogale Manasi,; Patil Kiran,; Mhatre Snehal,; Yadav Rakesh,; Mhatre Netra,; Gaikwad Kashish, (Asian Journal of Pharmaceutical Research and Development, 2026)
In situ gelling systems have recently garnered immense interest as an innovative method for increasing drug retention time, bioavailability, and efficacy. However, among the materials used in in situ gel formulations, natural polymers have emerged as an innovative substitute over synthetic polymers because of their superior biocompatibility, biodegradability, and safety profile. This review emphasizes on the use of various natural polymers in in situ gelling systems in terms of their gelation mechanism, physicochemical characterization, and pharmaceutical properties. Case studies from recently published reports illustrating the use of such polymers have also been included. The choice of natural polymers like alginate, chitosan, pectin, gellan gum, guar gum, and xanthan gum shows potential because they have high mucoadhesive properties, toxicity, and environmental sustainability. These biomaterials can be used in all routes of drug delivery. They also have less immunogenic potential, lack chronic toxicity, are potentially compliant with increased patient safety, and are readily biodegradable in comparison with synthetic polymers. The case studies included in this review highlight the use of natural polymer-based in situ gels for achieving targeted and sustained drug release with enhanced durability and therapeutic effects. In situ gelling systems containing natural polymers constitute a safer, more environmentally friendly, and highly efficient method over synthetic polymer-based in situ gels.